Coupling Coordination and Spatiotemporal Dynamic Evolution Between Green Urbanization and Green Finance: A Case Study in China - Dong, Guanglong; Ge, Yibing; Zhu, Weiya; Qu, Yanbo; Zhang, Wenxin (Frontiers in Environmental Science, 2021)
This study constructed a comprehensive index system and employed a coupling coordination degree model, global spatial autocorrelation models, and local spatial autocorrelation models to quantitatively investigate the spatiotemporal characteristics and dynamic mechanism of the coupling coordination relationship between green urbanization and green finance in China during 2010–2017. The results showed that the level of green urbanization and green finance improved over the study period, but the development of green finance lagged behind the pace of green urbanization and the comprehensive score was still low. The coupling coordination degree presented a trend of continuous optimization, with coordination in eastern China being clearly higher than in central, western, and northeastern China. Furthermore, there was both spatial dependency and spatial heterogeneity in the coupling coordination degree between green urbanization and green finance. Provinces with a high-high clustering mode were mainly distributed in the eastern region, while provinces in western and northeastern China mainly had a low-low clustering mode in 2010. The high-high clustering mode gradually expanded from eastern to central China, while most provinces in western and northeastern China still exhibited low-low clustering in 2017. This indicates that the coupling coordination degree between green urbanization and green finance had strong spatial agglomeration and spatial spillover effects in central and eastern China, while in western and northeastern China its development was still poor.